ANALYSIS OF LIQUIDITY RATIO, PROFITABILITY,AND SOLVABILITY TO EVALUATE THE PERFORMANCE OF PHARMACEUTICAL COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (BEI) DURING THE PERIOD 2021-2023 (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
This study aims to determine the effect of liquidity, solvency, and profitability ratios on company performance as measured by the return of pharmaceutical sector stocks in Indonesia and listed on the Indonesia Stock Exchange for the 2021-2023 period. The sample in this study is pharmaceutical sector companies listed on the Indonesia Stock Exchange in 2021-2023 and listing their financial statements on the Indonesia Stock Exchange in 2021-2023. The companies are Darya-Varia Laboratoria Tbk, Kalbe Farma Tbk, PT Pyridam Farma Tbk, PT Industri Jamu Dan Farmasi Sido Muncul Tbk, PT Soho Global Health Tbk, and Tempo Scan Pacific Tbk. The methods used in this study include quantitative methods and multiple linear regression analysis. The implications of this study show that the liquidity ratio with the current ratio and the profitability ratio with return on assets (ROA) have an influence on the performance condition of pharmaceutical sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. Meanwhile, the solvency ratio with the Debt to Asset Ratio (DAR) does not affect the Company's performance condition.
Keywords: Current ratio; Debt to Asset Ratio; Return on Assets; Company Performance